IMPLEMENTATION OF WASTE MANAGEMENT BY THE DEPARTMENT OF HOUSING RESIDENTIAL AND ENVIRONMENT IN SAGULING VILLAGE BAREGBEG DISTRICT CIAMIS REGENCY - Jeni Ramdani; Aan Anwar Sihabudin; Andang Andi (Faculty of Social And Political Science Universitas Galuh, 2020)
This research is motivated to determine the Implementation of Waste Management by the Public Housing Office of Kawasa Settlement and the Environment in Saguling Village Baregbeg District Ciamis Regency. The formulation of the problem is: How is the implementation of waste management by the Public Housing Service for Residential Areas and the Environment in the Village Saguling Baregbeg District, Ciamis Regency? How are the obstacles faced in the implementation of waste management by DPRKPLH in the Village SagulingBaregbeg District, Ciamis Regency? Efforts were made to overcome obstacles to implementing waste management by DPRKPLH in the Saguling Village Baregbeg District, Ciamis Regency? The objectives of the study were: To determine the implementation of waste management by DPRKPLH in the villageSagulingBaregbeg District, Ciamis Regency. This is to find out the obstacles faced by the implementation of waste management by DPRKPLH in Saguling Village, DistrictSagulingCiamis Regency. This is to determine the efforts made to overcome obstacles to implementing waste management by DPRKPLH in the villageSagulingBaregbeg District, Ciamis Regency. The research method used is the descriptive qualitative method. The results of research related to the Implementation of Waste Management by DPRKPLH, can be concluded: The coordination that has not been carried out is not comprehensive on a routine basis, there are too many officers in conducting socialization and there are no facilities provided by the DPRKPLH. The assistance provided to the community was not comprehensive. The coordination that is carried out must be following community culture, personal approach, and meetings held by DPRKPLH between the Village Government and the community.